2021
DOI: 10.3390/w13060828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Submerged Vane-Field on the Flow Pattern of a Movable Bed Channel with a 90° Lateral Diversion

Abstract: This laboratory study focused on the effect of a submerged vane-field on the flow pattern and bed morphology near and inside the entrance reach of a movable bed 90° lateral diversion. The system was modelled under live bed conditions for a water discharge ratio of ≈0.2. Two experiments were run until bed equilibrium was reached: with and without a vane-field installed close to the diversion entrance to control the transfer of sediments into the diversion channel. The equilibrium bed morphology and the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In addition to the above-mentioned structures, submerged vanes also have a broad range of applications for the reason that they can modify the local flow field, diverting the incoming flow from directly impinging on bridge piers or abutments and protecting river bend scour. Baltazar et al [29] used submerged vanes to change flow pattern in a lateral diversion under live bed conditions. The authors reported that the amount of sediment entering to diversion reduced up to 26% when vanes were in place.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above-mentioned structures, submerged vanes also have a broad range of applications for the reason that they can modify the local flow field, diverting the incoming flow from directly impinging on bridge piers or abutments and protecting river bend scour. Baltazar et al [29] used submerged vanes to change flow pattern in a lateral diversion under live bed conditions. The authors reported that the amount of sediment entering to diversion reduced up to 26% when vanes were in place.…”
Section: Introductionmentioning
confidence: 99%
“…Intake structures are used to divert water from channels and river systems for various purposes, such as energy production, irrigation, and domestic use [1][2][3]. Tyrolean and Coanda types of water intake structures are the most widely used bottom intake structures in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The discharge division ratio-Froude number relationship is proposed for subcritical dividing flows (Abderrezzak et al 2014). Moreover, the intake structure with submerged vane is used to optimize the hydrodynamic characteristics and control the sediment (Rahmani Firozjaei et al 2019;Baltazar et al 2021).…”
Section: Introductionmentioning
confidence: 99%